STUDY OF CORROSION PERFORMANCE OF ZINC COATED STEEL IN SEAWATER ENVIRONMENT - M, Ferry; N.I., Mohd Sukarnoor (Diponegoro University, 2013)
In this study, the corrosion protective mechanisms of zinc coating for mild steel in seawater were examined using weight loss, and electrochemical impedance spectroscopy methods (EIS). Coating is a technique to control the corrosion of a metal by providing an impervious metallic barrier by using sacrificial anode. The samples used in this study were fully zinc coated steel, zinc coated steel with scratch and mild steel as a control. Each sample undergoes the immersion process in seawater for 40 days. The results showed the corrosion rate of fully zinc coated steel decreases with immersion time from 0.03 mm/y to 0.01 mm/y and for zinc coated with scratch, from 0.034 mm/y to 0.012 mm/y. Impedance measurements studies revealed that fully zinc coated steel behave predominantly to be more practical anode in applying a great protection barrier for mild steel